BioSAXS on the SWING beamline at Synchrotron SOLEIL. Issue 6 (16th November 2021) - Thureau, Aurélien; Roblin, Pierre; Pérez, Javier
Abstract : This article describes recent developments on the SWING beamline for biological small‐angle X‐ray scattering (BioSAXS) experiments. Abstract : Small‐angle X‐ray scattering (SAXS) of proteins in solution has become a key tool for biochemists and structural biologists, thanks especially to the availability of beamlines with high‐throughput capabilities at synchrotron sources. Despite the large spectrum of scientific disciplines tackled on the SWING beamline since its opening in 2008, there has always been a strong commitment to offering state‐of‐the‐art biological SAXS (BioSAXS) instrumentation and data reduction methods to the scientific community. The extremely reliable in‐vacuum EigerX‐4M detector allows collection of an unlimited number of frames without noise. A small beamstop including a diamond diode‐based monitor enables measurements of the transmitted intensity with 0.1% precision as well as a q max / q min ratio as large as 140 at a single distance. The parasitic scattering has been strongly reduced by the installation of new hybrid blades. A new thermally controlled in‐vacuum capillary holder including fibre‐optics‐based spectroscopic functionalities allows the simultaneous use of three spectroscopic techniques in addition to SAXS measurements. The addition of a second high‐performance liquid chromatography (HPLC) circuit has virtually eliminated the waiting time associated with column equilibration. The easy in‐line connection of a multi‐angle light scattering spectrometer and a refractometer allows for an independent determination of the molecular mass and of the concentration of low‐UV‐absorption samples such as detergents and sugars, respectively. These instrumental improvements are combined with important software developments. The HPLC injection Agilent software is controlled by the SAXS beamline acquisition software, allowing a virtually unlimited series of automated SAXS measurements to be synchronized with the sample injections. All data‐containing files and reports are automatically stored in the same folders, with names related to both the user and sample. In addition, all raw SAXS images are processed automatically on the fly, and the analysed data are stored in the ISPyB database and made accessible via a web page.